Examining factors that influence the use of 3D gamification in e-learning in higher education/ Sakirin Muhamed and Nora'ayu Ahmad Uzir - Muhamed, Sakirin; Ahmad Uzir, Nora'ayu (Faculty of Information Management, 2022)
The acceptance and use of the latest technology are an important due to various factors, especially when Covid-19 dynamics hit the world today. It is quite a difficulty for most people in Malaysia when this change occurs and have to go through it which is called "New Norms". They need to get used to doing work or study online because they are not allowed to attend any classes or events. Indirectly, they have to master almost all activities through online means. Therefore, this study aims to understand the underlying factors that influence user satisfaction on the implications of 3D Gamification in eLearning. From the results of this study, we found that the results are as follows: (1) system quality, (2) service quality, (3) information quality, (4) perceived usability, (5) user satisfaction and (6) ease of use with the use of 3D gamification in e-Learning system. Data from 149 users have shown that satisfaction is influenced by the quality of service and the quality of information on the system. Surprisingly, service quality was found to be related to satisfaction. Lastly, the quality of information was found to influence user satisfaction rather than vice versa. Our findings support this implementation successfully make users easier to understand than the usual system used before.